UNDERSTANDING THE FACTORS INFLUENCING ACADEMIC MOBILITY OF FEMALE SCHOLARS IN PAKISTAN: A QUALITATIVE STUDY OF CHALLENGES AND MOTIVATIONS - Samina Akbar; Farhan Navid Yousaf; Dr. Ume Habiba (International Journal of Contemporary Issues in Social Sciences, 2024)
As academia increasingly embraces internationalization, it is crucial to explore the experiences of female scholars in the context of academic mobility. This research focuses on the intersection of gender and academic mobility, highlighting the unique challenges and opportunities faced by female scholars in Pakistan. The study aims to investigate the factors influencing the internationalization of education and gender discrimination experienced by female academics. The qualitative study includes female scholars from universities in Islamabad, Rawalpindi, Lahore, and Multan. Thirty participants were selected using purposive and snowball sampling techniques, and in-depth interviews were conducted for data collection, which was analyzed thematically. The research revealed that female academics encounter a range of issues while also gaining valuable knowledge and skills in modern education and research. Personal, professional, and economic factors motivate female academics to seek international educational opportunities. Gender discrimination is prevalent in academic mobility, with males often being preferred over females. Female scholars also face challenges related to travel, family responsibilities, and childcare while abroad. Despite these obstacles, they benefit from learning research skills and building relationships with international scholars.